2003
DOI: 10.1128/jcm.41.8.3784-3789.2003
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Swabs Are Appropriate Specimens for Diagnosis of Genital Tract Infection with Chlamydia trachomatis

Abstract: NAATs were performed on FCU, urethral, cervical, self-and clinician-collected VS. Sensitivity was compared to isolation using cervical and urethral swabs. Agreement of NAAT results between VS and cervical swabs or FCU was calculated. Specimens from 2,517 15-to 25-year-old asymptomatic women attending clinics at nine different centers were evaluated. Results with self-and clinician-collected VS were equivalent and were at least as good as results with FCU and cervical swabs. Across all sites, summary specificit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(119 citation statements)
references
References 16 publications
8
103
0
8
Order By: Relevance
“…Recent studies have shown that PCR testing for Chlamydia using self-collected vaginal swabs is just as sensitive as using endocervical specimens (Garrow et al, 2002;Schachter et al, 2003). Detection rates of target organisms using self-collected vaginal swabs in this study were similar to those for endocervical specimens.…”
Section: -34 (N536)supporting
confidence: 68%
“…Recent studies have shown that PCR testing for Chlamydia using self-collected vaginal swabs is just as sensitive as using endocervical specimens (Garrow et al, 2002;Schachter et al, 2003). Detection rates of target organisms using self-collected vaginal swabs in this study were similar to those for endocervical specimens.…”
Section: -34 (N536)supporting
confidence: 68%
“…non è mai stata una metodica di routine perché decisamente complessa, costosa e non standardizzabile. La coltura cellulare è stata per lungo tempo considerata il "gold standard" poiché ha una specificità del 100%, ma la sua sensibilità varia dal 50 al 90% secondo i diversi studi (1,8,47,101). La sensibilità è legata anche al numero di microrganismi presenti nel campione e al loro stato replicativo: la presenza di una forma persistente di C.t.…”
Section: Prelievo Oculareunclassified
“…Più recentemente sono stati introdotti nella pratica diagnostica, test basati sull'amplificazione di acidi nucleici (NAATs). L'amplificazione del genoma permette di produrre un numero molto elevato di sequenze geniche identiche e di migliorare la sensibilità del test (101). Questi metodi amplificano sia un gene cromosomico, il gene omp 1 codificante per il MOMP, sia l'RNAr presente in circa 1000 copie per microrganismo, sia una sequenza del plasmide criptico specifico di C.t.…”
Section: Metodi Immunoenzimatici (Eia)unclassified
See 1 more Smart Citation
“…[2][3][4] Other studies (non-ED based) have shown that vaginal swab specimens perform as well as, or better than, urine or cervical samples for STI detection. [5][6][7] To the best of our knowledge, self-administered vaginal swabs (SAVS) have only been evaluated in non-ED settings. Our objective was to examine the feasibility of SAVS in identifying C. trachomatis and N. gonorrhoeae in female ED patients.…”
mentioning
confidence: 99%